Komparatif Teori Perkembangan Peserta Didik Menurut Barat dengan Islam dan Implikasinya dalam Pendidikan Islam - Asnawan Asnawan (FALASIFA : Jurnal Studi Keislaman, 2017)
This paper is about the developmental theory of learners in the view of the West and Islam in the education holders of parents' trust, and as one of the implementers of Islamic education teachers are not only tasked to provide scientific education. The task of the teacher should be a continuation and synchronization with the parent's duties, which is also the task of educators in general, that is to provide a human-oriented education as a whole. It can be realized by making man as a human being, maintaining the nature of humanity, and maintain the fitrah that has been given by Allah SWT. So the teacher should deliver lessons with easy language and try to make the students understand the lesson.Keywords: Komparatif, Teori Perkembangan, peserta didik, Barat & Islam